A NEW SPECIES OF MEXICANA (MONOGENEA: DACTYLOGYRIDAE) PARASITIC ON TWO SPECIES OF ANISOTREMUS (PERCIFORMES: HAEMULIDAE) FROM THE BRAZILIAN COASTAL ZONE - Dias Cezar, Anderson (2012)
Mexicana anisotremum n. sp. (Monogenea) a gill filaments parasite of two species of fishes of the genus Anisotremus from the coast of the state of Rio de Janeiro, Brazil (approx. 21-23º S, 42-45º W), is described and illustrated. The monogeneans were collected from 32 specimens of Anisotremus virginicus (Linnaeus, 1758), and 13 specimens of A. surinamensis (Bloch, 1791) (Haemulidae). The new species of Mexicana, differs from M. atlantica Luque, Amato & Takemoto, 1992 by: 1. presence of a sclerotized structure with six spines in vaginal vestibule; 2. absence of bilobed testes; and 3. Presence of copulatory organ without sclerotized piece at its base.